Developing competence and confidence in midwifery-focus groups with Swedish midwives. Issue 1 (February 2017) - Bäck, Lena; Hildingsson, Ingegerd; Sjöqvist, Carina; Karlström, Annika
Abstract: Background: Midwives have a significant impact on the clinical outcome and the birthing experience of women. However, there has been a lack of research focusing specifically on clinical midwives' learning and development of professional competence. Aim: The objective of the study was to describe how midwives reflect on learning and the development of professional competence and confidence. Methods: A qualitative study based on focus groups with midwives employed in maternity services. Findings: Four categories describe the results: (1) Feelings of professional safety evolve over time; (2) Personal qualities affect professional development; (3) Methods for expanding knowledge and competence; and (4) Competence as developing and demanding. The meaning of competence is to feel safe and secure in their professional role. There was a link between the amount of hands-on intrapartum experience and increasing confidence that is, assisting many births made midwives feel confident. Internal rotation was disliked because the midwives felt they had less time to deepen their knowledge and develop competence in a particular field. The midwives felt they were not seen as individuals, and this system made them feel split between different assignments. Discussion: External factors that contribute to the development of knowledge and competence include the ability to practise hands-on skills in an organisation that is supportive and non-threatening. Internal factors include confidence, self-efficacy, and a curiosity for learning. Conclusions: Midwives working within an organisation should be supported to develop their professional role in order to become knowledgeable, competent and confident.